1987
DOI: 10.1111/j.1439-0329.1987.tb01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the fungi associated with damping‐off in the regeneration of Eucalyptus obliqua and E. radiata in a central Victorian forest

Abstract: BIESBROCK, J. A.;BOHLOOL, B. B.;MARX, D. H., 1974: Study of mycorrhizae by means of fluorescent antibody. Can. J. Microbiol. 20, 137-139. ZoLLFRANK, U., 1986: Inimunhistochemischer Nachweis von Armillaria sp. und Heterobasidion annosum an infizierten Fichten. Doctoral thesis. Technical University of Munich. ZOLLFRANK, U.; HoCK, B., 1987: Infection of Norway spruce by Armillaria under defined conditions. Submitted to Eur. AbstractSoil baiting techniques identified the presence of five fungal genera capable of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
(4 reference statements)
0
7
1
Order By: Relevance
“…This probably resulted from pathogenic fungi, a previously reported cause of winter mortality of eucalypt seedlings (Grose 1957;Cunningham 1960;Mwanza & Kellas 1987). Mwanza and Kellas (1987) found that damping-off deaths of Eucalyptus obliqua and Eucalyptus radiata occurred within the first 8 weeks after emergence. Their seedlings were affected by seedbed conditions and overstorey density and deaths were caused mostly by Pythium and Eusarium.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This probably resulted from pathogenic fungi, a previously reported cause of winter mortality of eucalypt seedlings (Grose 1957;Cunningham 1960;Mwanza & Kellas 1987). Mwanza and Kellas (1987) found that damping-off deaths of Eucalyptus obliqua and Eucalyptus radiata occurred within the first 8 weeks after emergence. Their seedlings were affected by seedbed conditions and overstorey density and deaths were caused mostly by Pythium and Eusarium.…”
Section: Discussionmentioning
confidence: 93%
“…Accepted for publication August 1993. fungi, low light intensities and frost (Cunningham 1960;Mwanza & Kellas 1987;Battaglia & Wilson 1990). \n Eucalyptus marginata Donn ex Smith (jarrah) seedlings a trend has been shown for mortality to be greater in uncultivated seedbeds, in seedbeds with groundcover vegetation and litter, and where there was grazing by native vertebrates (Abbott 1984;Abbott & Loneragan 1986).…”
Section: Introductionmentioning
confidence: 95%
“…Species of Penicillium are often associated with post-harvest diseases [5] or are pathogenic on intact growing plants [6]. P. olsonii is among the rarest clearly distinct species of the genus Penicillium [7] and was described in association with a damping-o¡ disease of eucalyptus seedlings [8]. P. olsonii can also infect intact leaves of Arabidopsis thaliana and secretes PGs during the infection process (W. Scha «fer, unpublished results).…”
Section: Introductionmentioning
confidence: 99%
“…Biotic factors included seed harvesting, which has already been mentioned. In addition, soil pathogens may cause mortality (Mwanza and Kellas 1987), and allelopathic effects may restrict emergence levels, but its importance depends on the species, the amount and types of litter, soil properties and climate (May and Ash 1990). Direct effects included seedbed conditions and overstorey density.…”
Section: Basic Mechanisms Of Seed Dispersal and Seedling Establishmentmentioning
confidence: 99%